2014
DOI: 10.1007/s11270-014-2058-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Linear Regression and Artificial Neural Networks to Predict Time and Efficiency of Soil Vapor Extraction

Abstract: The prediction of the time and the efficiency of the remediation of contaminated soils using soil vapor extraction remain a difficult challenge to the scientific community and consultants. This work reports the development of multiple linear regression and artificial neural network models to predict the remediation time and efficiency of soil vapor extractions performed in soils contaminated separately with benzene, toluene, ethylbenzene, xylene, trichloroethylene, and perchloroethylene. The results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In fact, multiple linear regression (MLR) can also be used for predicting a target parameter of samples in the situation where the number of wavelengths is less than the number of samples [ 31 ]. MLR is a classic linear algorithm and works to interpret linear relationship between one dependent variable and two or more independent variables [ 32 ]. In this study, based on the same selected optimal wavelengths, four MLR models including RC-NC-MLR, SR-NC-MLR, SPA-NC-MLR, and CARS-NC-MLR were respectively developed and assessed in terms of r and RMSE values.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, multiple linear regression (MLR) can also be used for predicting a target parameter of samples in the situation where the number of wavelengths is less than the number of samples [ 31 ]. MLR is a classic linear algorithm and works to interpret linear relationship between one dependent variable and two or more independent variables [ 32 ]. In this study, based on the same selected optimal wavelengths, four MLR models including RC-NC-MLR, SR-NC-MLR, SPA-NC-MLR, and CARS-NC-MLR were respectively developed and assessed in terms of r and RMSE values.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al [7] found that higher flow rates did not significantly improve removal rates, and pulsed and continuous vapor extraction had almost the same contaminant removal effects in the sand column. Albergaria et al [8] used multiple linear regression and artificial neural network models to predict the remediation time and SVE efficiency. Wang et al [9] proposed that the vacuum degree of an SVE system is not linearly related to the extraction flow rate and that an optimal value exists.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution often experiences a high enough increase to have an impact on environmental pollution and human health [1]. Broadly speaking, the perceived health impacts are respiratory problems [2]. Related to this, the negative effects that will be felt in the future are damage to the lungs, heart, and other organs [3].…”
Section: Introductionmentioning
confidence: 99%